2007
DOI: 10.1002/psc.885
|View full text |Cite
|
Sign up to set email alerts
|

1,4‐Diazepine‐2,5‐dione ring formation during solid phase synthesis of peptides containing aspartic acid β‐benzyl ester

Abstract: The Fmoc-based SPPS of H-Xaa-Asp(OBzl)-Yaa-Gly-NH(2) sequences results in side reactions yielding not only aspartimide peptides and piperidide derivatives, but also 1,4-diazepine-2,5-dione-peptides. Evidence is presented to show that the 1,4-diazepine-2,5-dione derivative is formed from the aspartimide peptide. The rate of this ring transformation depends primarily on the tendency to aspartimide and piperidide formation, which is influenced by the nature of the amino acid following the aspartic acid beta-benzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 5 publications
1
13
2
Order By: Relevance
“…Hence, not only adjacent Yaa but also the residue Xaa has a certain contribution to the observed level of Asi at the Xaa‐Asp‐Yaa motif and consequently of N‐terminal DKP. A similar observation was previously described for DKD formation from Asp β ‐benzyl esters …”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…Hence, not only adjacent Yaa but also the residue Xaa has a certain contribution to the observed level of Asi at the Xaa‐Asp‐Yaa motif and consequently of N‐terminal DKP. A similar observation was previously described for DKD formation from Asp β ‐benzyl esters …”
Section: Resultssupporting
confidence: 72%
“…Aspartimides are ubiquitous by‐products in peptides with the Asp‐Yaa motif synthesized via Fmoc‐SPPS. It is thus conceivable that both a seven‐membered DKD following pathways A or B in Scheme and/or a six‐membered DKP following pathway C can be formed . However, the formation of a seven‐membered DKD was not observed in this study.…”
Section: Resultscontrasting
confidence: 60%
See 2 more Smart Citations
“…The α-amino acids were initially immobilized on a Wang resin via a carboxylate group, and the desired scaffold was formed by cyclative cleavage upon acylation with β-amino acids. Similarly, it was found that using aspartic acid β-benzyl ester in Fmoc-based solid-phase peptide synthesis not only risks the formation of the aspartimide peptide but also results in its further transformation into a 1,4-diazepane-2,5-dione-peptide derivative [96].…”
Section: 4-diazepane-25-dionesmentioning
confidence: 98%